IMPLEMENTASI PERATURAN PEMERINTAH SUMBAWA NOMOR 22 TAHUN 2020 TENTANG PENANGGULANGAN KEMISKINAN DI KABUPATEN SUMBAWA TAHUN 2021 - Irawansyah, Irawansyah (Yayasan Nusantara Hasana Berdikari, 2025)
Poverty is a condition of inability to meet basic needs such as food, clothing, shelter, education, and health. The implementation of Sumbawa Regency Government Regulation Number 22 of 2022 concerning poverty alleviation in Sumbawa Regency is expected to reduce the poverty rate in Sumbawa Regency. This study uses descriptive qualitative research methods and data collection techniques using observation, interview and documentation techniques. This study uses the theory of policy implementation from Ripley & Franklin. The results of the study show that the poverty line in Sumbawa can really be the center of attention. To measure the poverty line, the Central Statistics Agency (BPS) uses the concept of the ability to meet basic needs (basic needs approach), namely the inability from an economic perspective to meet basic food and non-food needs as measured by expenditure. Referring to a survey conducted by the United Nations (UN), recording expenditure tends to better describe the economic condition/purchasing power of a household compared to information related to income which tends to be unreliable. The conclusion of this study is that in 2021, there was a spike in poverty due to the outbreak. However, the government optimized its efforts by creating programs to minimize the problem of poverty so that it did not increase significantly, one of which was the Direct Cash Assistance (BLT). This program, one of the programs implemented by the government in 2021, ran smoothly. According to the Statistics Indonesia (BPS), the poverty rate in 2022 again experienced a significant decline of 1.92% to 64,730 people. This decline in the poverty population in 2022 was the fastest compared to previous years.